TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL INNOVATION: THE MEDIATING EFFECT OF POSITIVE PSYCHOLOGICAL CAPITAL - Sengullendi, M. Fatih; Efe, Mehmet Naci; Sehitoglu, Yasin (FUTURE ACAD, 2019)
The aim of the research is to find out whether there is a relationship between the transformational leadership style behaviors perceived by white-collar employees currently working in Turkish Standards Institution (TSI) and organizational innovation of the firm. Furthermore, in the study, we examined whether the positive psychological capital of employees has a mediating effect on this relationship. 1200 white-collar employees working in TSI have constituted the sample of the research, 325 of them have been reached via the survey. The surveys consist of samples aimed at obtaining demographic information of the participants and measuring their transformational leadership perceptions, organizational innovation, and positive psychological capital. 296 feedbacks were received related to surveys and 278 of them were approved to be sufficient to be used within the scope of the survey study. SPSS 22.0 statistical software package has been used in order to analyze the data of the study. First, frequency analyses were applied in the scope of the demographic characteristics of participants, and then the exploratory factor analysis, reliability analysis, and the correlation analysis were applied within the scope of the answers to the scales used, and finally, the hypothesis tests were applied. The result of the study showed the relationship between the transformational leadership and the organizational innovation. And also, the research has revealed that the positive psychological capital has a mediating role in the relationship between the transformational leadership style and the organizational innovation. (C) 2019 Published by Future Academy www.FutureAcademy.org.UK
Keywords: Transformational leadership; positive psychological capital; organizational innovation; turkish standards institution; Business & Economics